A case of gastrointestinal stromal tumour mimicking uterine fibroid - Nurhayati A; Aida Hani Mohd Kalok; Nik Muhd Aslan Abdullah; Reena Rahayu Md Zain; Ani Amelia Zainuddin (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Gastrointestinal stromal tumour (GIST) is extremely rare with reported incidence of 20 per million per year. It is the most common mesenchymal tumour of the gastrointestinal tract. When it occurs at the pelvis in a female patient, it can be misleading to a gynaecological diagnosis. Non gynaecological diagnosis such as GIST must be considered in patients with pelvic mass presenting with atypical symptoms.